Bel Sekolah Otomatis Berbasis Arduino yang Dikontrol Menggunakan Aplikasi Mobile - Muh Pauzan; Indri Yanti (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2021)
The school bell is one of the important devices in school. It has been used from years ago to the present. Bell has been improved along with time. Nowadays, research about school bell has been focused on the bell’s controller, such as using software in a computer, placing a keypad on the bell, and even controlling the bell’s schedule, which can only be performed using coding. However, these controllers are not practical; therefore, an efficient school bell is made by using an Android-based application as the controller. Bluetooth is used as a communication tool between the smartphone and the bell. The research method was by conducting a literature study and doing a survey to SDN 1 Sarapati Indramayu. Based on the method, it has been decided to make four modes on the Android application, i.e., regular mode, exam mode, free, dan emergency mode. Regular mode is used in a normal condition, and exam mode is used when the students are doing an exam. If teachers want to ring the bell directly, the free mode is operated. There are four types of bell ring in free mode, i.e., once, twice, three, and four-time rings. Emergency mode is useful when the school is in an emergency, such as earthquakes, floods, and fires. Results show that the maximum range to control the bell is 9 m.